STEM CELLS OF ENDOCRINE GLANDS - Deltsova, O.I.; Geraschenko, S.B.; Chaikovsky, Yu.B. (World of Medicine and Biology, 2013)
The article presents current views on stem cells of endocrine glands in adults - pituitary, thyroid, parathyroid, and adrenal gland. Multipotent stem/progenitor cells of adenohypophysis are follicular stellate cells which express the S100, Sox9, Sox2 and Oct4, in culture form the primary and secondary "pituispheres". Pituitary progenitor cells of neurohypophysis by markers resemble oligodendrocyte progenitor cells. In the thyroid gland of adults stem cells and progenitor cells of endodermal origin for T-thyrocytes are identified. They express ABCG2, nucleostemin and Oct4. C-thyrocytes express markers of neural tissue (Connexin43-LacZ, Wnt1-Cre/R26R, TuJ1, neurofilaments160, nestin, P75NTRі and Sox10). The surface of stem cells in parathyroid glands is positive for CD73, CD166, CD29, CD49a, CD49b, CD49d, CD44, CD105 and MHC class I. Stem cells of adrenal gland are localized in its cortex periphery and compose 0,01-0,64% of all cells in subcapsular zone. Their genetic analysis identified key signaling pathways Shh and Wnt, Wnt/B-Catenin. Evidence of progenitor cells subpopulation in the adrenal medulla of adults is presented. In perspective grown in culture endocrine progenitor cells of humans can be used to restore functions of endocrine glands.